Effective classroom management : - Garrett, Tracey (Teachers College Press, 2014)
This user-friendly resource will help K–12 teachers become more effective classroom managers. Tracey Garrett provides a new perspective that has been well received by thousands of preservice, novice, and veteran teachers. Each chapter of the book concentrates on a key area (physical design, rules and routines, relationships, engaging instruction, and discipline) and focuses on the importance of that particular area in relation to a teacher’s overall classroom management plan. Examples of specific techniques and strategies are presented through three classroom teachers, each representing a different grade level. In addition, four students share their beliefs and experiences related to the different aspects of classroom management and provide unique insight into the lived experience of students in real classrooms in a variety of contexts, including urban and suburban schools.